Specialised and professional discourse across media and genres - Giuliana Garzone (Ledizioni, 2017)
This book deals with discursive aspects of specialised communication, looking in particular at the role and scope of language and discourse in professional practice across a variety of fields and modes. Its chapters are diverse in their outlooks, analytical procedures, and object of enquiry, and span across different specialised domains, settings, genres, and media (from face-to-face communication to television, from traditional websites to social networking sites). In broad terms, they are all set in a discourse-analytical framework and share the ultimate purpose of providing new insights into the evolution of discourse practices used by professionals in a variety of specialised genres at a time characterised by rapid scientific and dramatic technological advances accompanied by important societal, sociotechnical and cultural transformations. Professional and workplace routines and procedures are embedded in a dense network of discursive practices, which both determine and reflect professional roles, knowledge, expertise, positions and tasks at any given moment in time. Thus, when experts communicate with the general public, a display of competence in the specialised register of the relevant domain is of the essence. This need for discursive competence, in addition to professional expertise, is generally acknowledged also in education and training. The essays gathered in this volume bear out this view, and collectively aim to contribute to the discursive study of professional practices by providing insights into the multiple ways in which discourse partakes of them.